Successful business intelligence implementation: a systematic literature review. Issue 2 (2nd September 2019) - El-Adaileh, Nadeem Ali; Foster, Scott
Abstract : Purpose: The purpose of this paper is to present a systematic literature review to determine the factors that relate to successful business intelligence (BI) system implementation. Design/methodology/approach: The study has a collection of literature that highlights potential references in relation to factors for system implementation in relation to BI. There is the employment of "content analysis", given that the study purpose is the achievement of deep understanding of the variety of factors of implementation that other researchers have previously identified. Findings: An initial investigation of 38 empirical studies on the implementation of BI led to ten factors being compiled. Difficulties in implementation were found to exist in relation to the operationalisation of large numbers of factors within organisations. The implementation factors were analysed and then sorted into a descending order based upon their frequency of occurrence. Research limitations/implications: The research is limited to consider BI implementation factors. Moreover, literature is collected from selected databases and journals from 1998 to 2018. Practical implications: Researchers of BI may, within the future, develop models for the measurement of the implementation level of BI within industries along with the sustaining of them. Moreover, work-based learning industries can benefit by adopting the results of this study for the effective implementation of BI. The implementation factors can be seen as key constructs upon which there may be the undertaking of more statistical analyses. Originality/value: The original output from this research can help researchers' in the future in enhancing identification of studies that are relevant for the review of literature for their research.